Sensory Descriptive Analysis and Investigation of Consumer Acceptance of Bavarian Wheat Beer - Schmelzle, Annette; Lindemann, Bernd; Methner, Frank-Jürgen (BrewingScience, 2013)
The purpose of this research on wheat beer was to identify the most important acceptance-causing sensory attributes for wheat beer. For this reason, specific attributes were developed and 18 wheat beers were analysed in a sensorily descriptive format. The determination of acceptance was achieved by testing products in the target group (n=148). Twelve wheat beers were evaluated, which were chosen for their sensory properties. By linking sensory description and acceptance values, significant attributes for wheat beer that are responsible for acceptance were detected. Subsequently, split analyses based on gender, age and consumption intensity were performed. Wheat beers can be described using twenty sensory terms, which demonstrates that there is great product diversity. Wheat beers indicate different sensory qualities: fruity, non-fruity, bitter and mouthcoating, tingly or sweet and creamy. Wheat beers with a creamy mouthfeel were preferred by consumers, while bitter and non-fruity-smelling wheat beers were not well-liked. In investigating the acceptance of various sub-groups, it was discovered that women had a greater preference for wheat beers with a creamy mouthfeel than did men. In comparison to younger beer consumers, consumers over the age of 40 showed no differentiation in their acceptance of wheat beers. On the other hand, beer drinkers under 40 years preferred ?creamy? wheat beers with a banana-like odour. Wheat beers with an above-average rating for the attribute ?banana? were significantly more often preferred amongst consumers who drink wheat beer two to three times a month or more than by consumers who drink wheat beer only once a month or less.